Fulfillment of Labor Rights for Persons with Disabilities in Indonesia - Nazifah; Mangku, Dewa Gede Sudika; Yuliartini, Ni Putu Rai (International Journal of Criminology and Sociology, 2021)
The purpose of this research is to fulfill the rights of persons with disabilities to obtain jobs following their fields without reducing their rights. The research method used is normative juridical with literature study. Decent work is a right for every human being without exception. Various racial, ethnic, and religious backgrounds that are part of a human’s identity do not become a barrier for him to get his right. Likewise with the physical or non-physical conditions that underlie a human being. Every human being who has a certain physical or non-physical background also has the same rights to get decent work, including persons with disabilities. The State of Indonesia ratified the Convention on the Rights of Persons with Disabilities into Law Number 19 of 2011. In the preamble of the law, it was explained that the countries that signed the convention had the obligation to promote and protect the rights and dignity of persons with disabilities and promote their participation in the civil, political, economic, social, and cultural spheres is based on equal opportunities, meaning that the Indonesian Government is obliged by law to fulfill the rights of persons with disabilities, especially about the right to work in Indonesia.